UPAYA PERBAIKAN SIFAT FISIKOKIMIA TEPUNG UBI KAYU MELALUI PROSES FERMENTASI SAWUT UBI KAYU DENGAN STARTER BAKTERI ASAM LAKTAT LACTOBACILLUS CASEI DAN PEMANFAATANNYA SEBAGAI BAHAN BAKU SNACK TRADISIONAL PILUS DAN ROTI MUFFIN - Kusumaningrum, Annisa; Sumardiono, Siswo (METANA, 2012)
Cassava is one of the biggest commodity in Indonesia which is the total amount of its production is 24,080,000 ton/year. This huge amount of cassava can be used as cassava flour so that it could have similar characteristics with wheat flour. Therefore, in this research the cassava is being modified by fermentation method using the lactic acid bacteria starter,i.e Lactobacillus casei. While the cassava grate is being fermented, the enzyme that could destroy the cassava cell is produced by bacteria so it cause the degradation of starch granula. This condition changes of the physiochemical characteristic of cassava flour produced. The purpose of this research determines the best condition from the variables concentration of lactic acid bacteria starter and fermentation time of the cassava grate to physiochemical characteristic of cassava flour. The best conditions of cassava flour is fermentation time of 48 hour and 6% v/v Lactobacillus casei concentration. Physiochemical characteristic of cassava flour best treatment is the swelling power of 14.13, level of expand â€œpilusâ€ snack 596.399%, baking expansion 2.28 cm /g and hardness of 3 muffin cake was 620.262 gf. Keywords: cassava fermentation, Lactobacillus casei, physiochemical characteristic, fermentation time, concentration of lactic acid bacteria starter